Recent Advances in Astaxanthin as an Antioxidant in Food Applications - Yimeng Dang; Zhixi Li; Fanqianhui Yu (MDPI AG, 2024)
In recent years, astaxanthin as a natural substance has received widespread attention for its potential to replace traditional synthetic antioxidants and because its antioxidant activity exceeds that of similar substances. Based on this, this review introduces the specific forms of astaxanthin currently used as an antioxidant in foods, both in its naturally occurring forms and in artificially added forms involving technologies such as emulsion, microcapsule, film, nano liposome and nano particle, aiming to improve its stability, dispersion and bioavailability in complex food systems. In addition, research progress on the application of astaxanthin in various food products, such as whole grains, seafood and poultry products, is summarized. In view of the characteristics of astaxanthin, such as insolubility in water and sensitivity to light, heat, oxygen and humidity, the main research trends of astaxanthin-loaded systems with high encapsulation efficiency, good stability, good taste masking effect and cost-effectiveness are also pointed out. Finally, the possible sensory effects of adding astaxanthin to food aresummarized, providing theoretical support for the development of astaxanthin-related food.